Hope in Life: A Comparative Study among Yoga Practitioners and Non-Practitioners - Chandran K, Madhava; P, Unniraman; K, Sasidharan; KK, Unnikrishnan (Journal of Medical Health Research and Psychiatry, 2024)
This article reports the results of a comparative study on hope in life of yoga practitioners and non-practitioners carried out among 100 yoga practitioners and 100 people who do not do yoga in India using a questionnaire containing the measure of hope in life and the characteristics of the yoga respondents such as age, period of yoga practice, whether faced any psychological problems during the past two months and whether faced any other problems in life during the past two months. The findings reveal that the yoga practitioners have experienced all the hope related parameters comparatively better than non-practitioners. Statistically significant difference in the scores between yoga practitioners and non-practitioners for many of the parameters is also evident. The characteristics, namely, age of the yoga practitioners, period of yoga practice, level of psychological problems, and level of other problems they faced during the past two months contribute to 88.7 % variation in their hope score. Statistically significant difference is observed in the hope score of yoga practitioners under different categories of age and the level of other problems faced in life during the past two months. It will worthwhile if yoga centres in different countries undertake relevant studies on relaxation techniques like yoga, meditation etc. with the help of experts and transfer the results to as many people as possible in order to motivate them to practice these methods and achieve better meaning and wellbeing in their lives.